INCOME SMOOTHING PRACTICE ON MANUFACTURING COMPANIES IN INDONESIA - Stewart, Stewart; Siahaan, Magda (E-Jurnal Akuntansi TSM, 2024)
This study seeks empirical evidence regarding the influence of profitability, company size, financial leverage, stock price, cash holding, dividend payout ratio, and audit committee. This study uses data from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The sample amounted to 129, obtained by the purposive sampling method. The hypothesis of this study was carried out using binary logistic analysis. The study's results for profitability, cash holding, stock price, and financial leverage show that they do not influence income smoothing practices. Apart from the variables above, the dividend payout ratio and audit committee positively affect income smoothing practices. In contrast, company size hurts income-smoothing practices. The positive influence states that the greater the dividend payout ratio and audit committee, the greater the influence of company management to carry out income smoothing practices, while for the negative influence, the larger the company's size, the lower the income smoothing practices in the company will be.